Production and storage of biohydrogen during sequential batch fermentation of Spirogyra hydrolyzate by Clostridium butyricum. (August 2015) - Ortigueira, Joana; Pinto, Tiago; Gouveia, Luísa; Moura, Patrícia
Abstract: The biological hydrogen production from Spirogyra sp. biomass was studied in a SBR (sequential batch reactor) equipped with a biogas collecting and storage system. Two acid hydrolysis pre-treatments (1N and 2N H2 SO4 ) were applied to the Spirogyra biomass and the subsequent fermentation by Clostridium butyricum DSM 10702 was compared. The 1N and 2N hydrolyzates contained 37.2 and 40.8 g/L of total sugars, respectively, and small amounts of furfural and HMF (hydroxymethylfurfural). These compounds did not inhibit the hydrogen production from crude Spirogyra hydrolyzates. The fermentation was scaled up to a batch operated bioreactor coupled with a collecting system that enabled the subsequent characterization and storage of the biogas produced. The cumulative hydrogen production was similar for both 1N and 2N hydrolyzate, but the hydrogen production rates were 438 and 288 mL/L.h, respectively, suggesting that the 1N hydrolyzate was more suitable for sequential batch fermentation. The SBR with 1N hydrolyzate was operated continuously for 13.5 h in three consecutive batches and the overall hydrogen production rate and yield reached 324 mL/L.h and 2.59 mol/mol, respectively. This corresponds to a potential daily production of 10.4 L H2 /L Spirogyra hydrolyzate, demonstrating the excellent capability of C. butyricum to produce hydrogen from microalgal biomass. Highlights: Production of biohydrogen from crude Spirogyra hydrolyzates. Set-up of a collecting and storage system for continuous biogas sampling. The hydrogen production rate is 324 mL/L.h in the SBR (sequential batch reactor). The SBR produces daily an equivalent to 10.4 L H2 /L of crude Spirogyra hydrolyzate.